The Effect of Grip Strength on Bone Mineral Density Measurements in Postmenopausal Sedentary Women - Filiz Sivas; Fatma Yazıcı; Kürşat Özoran (Archives of Rheumatology, 2009)
Objective: The present study aimed to investigate the effect of grip strength on dominant and non-dominant forearm, hip and lumbar bone mineral density (BMD) measurements in postmenopausal women. Material and Methods: A total of 93 postmenopausal women (age range: 50-70 years) were included in the study. The dominant extremity was determined by querying patients regarding which hand they use while eating or performing a task. Following measurements regarding height and body weight for body mass index (BMI), grip strength was measured in all patients using the Jamar hand dynamometer device. BMD measurements were determined in the dominant and non-dominant forearm ultradistal end (UDE), 1/3 radius distal end (RDE) and forearm total, and dominant and non-dominant side femur neck, total hip, and lumbar L1-4 regions. Results: When the hand grip strengths of dominant and nondominant extremities were compared along with the forearm BMD values, only the hand grip strength of the dominant side was significantly higher than the non-dominant side. There was a significant correlation between the dominant and nondominant extremity RDE, UDE, and forearm total BMD measurements and the grip strength of the same side. The multivariate regression analyses revealed that the determining effect of grip strength on the forearm BMD measurements of the dominant and non-dominant extremities was weak. There was also a correlation between L1-4 total, dominant and non-dominant extremity femur neck and total hip BMD values and the hand grip strengths. However, the regression analyses revealed that grip strength did not have a determining effect on L1-4 total and dominant and non-dominant extremity hip BMD values. The factors affecting BMD values of these regions were detected as BMI, age and duration of menopause. Conclusion: The present study concluded that the effect of muscle strength on BMD measurements in postmenopausal sedentary women was site-specific rather than systemic. (Turk J Rheumatol 2009; 24: 21-6)